Transport of pathogens through saturated porous rocks with variable flow and salinity - Valentina Prigiobbe; Maria Clementina Caputo; Osvalda De Giglio; Antonella Francesca Savino; Antonietta Celeste Turturro; Debora Colella; Mert Ekiz Cetin; Lorenzo De Carlo; Francesco Bagordo; Tiziana Grassi; Giorgio Cassiani; Mirco Milani; et al. (Journal of Contaminant Hydrology, 2026)

Understanding benefits and risks of exploiting spring habitats by subterranean animals: insights from a mark-recapture study on the olm (Proteus anguinus) - Benedetta Barzaghi; Giorgio Grassi; Thomas Creanza; Magdalena Gajdošová; Veronica Zampieri; Stefano Lapadula; Matteo Galbiati; Gergely Balázs; Danilo Borgatti; Valentina Balestra; Valeria Messina; Edgardo Mauri; et al. (Hydrobiologia, 2026)
The olm (Proteus anguinus ) is an iconic predator in underground ecosystems, but it also exploits localized spring habitats, characterized by higher trophic abundance and predation risk. This study analyzes the advantages and disadvantages of using springs and caves, with particular attention to population variations. In the classical karst system (NE-Italy), we compared food availability and predator occurrence in 40 springs and 8 caves and monitored 76 P. anguinus individuals through capture-\mark-recapture (CMR) surveys. Individuals captured in springs had a significantly higher Scaled Mass index (SMI) compared to those from caves, with no significant differences in the occurrence of injuries. The greater trophic abundance and diversity in springs, combined with site fidelity, suggests that karst spring ecotones may represent critical foraging areas for stygobionts, such as animals specialized to inhabit groundwater. The results confirm the ecological importance of these karstic springs habitats, which support high biodiversity, species interactions, and serve as key points for studying the adaptive responses of Proteus anguinus and other subterranean species.

Unlocking extra virgin olive oil identification: predicting ethyl esters with explainable AI on IR spectra - Michele Magarelli; Silvia Grassi; Giacomo Squeo; Pierfrancesco Novielli; Roberto Bellotti; Francesco Caponio; Cristina Alamprese; Sabina Tangaro (Food Chemistry, 2026)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Ensembling satellite monitoring and numerical cartography towards the safety assessment of infrastructures - Francesca Grassi; Paolo Rossi; Benedetta Brunelli; Francesco Mancini; Cristina Castagnetti; Loris Vincenzi; Elisa Bassoli; Alessandro Capra (Applied Geomatics, 2025)
This paper explores new technologies that can advance the state-of-the-practice in safety assessment and health monitoring of existing infrastructures. In this context, multi-temporal interferometric Synthetic Aperture Radar techniques combined with the use of digital models of infrastructures represent a powerful integration to conventional approaches in the monitoring and assessment of structural safety of infrastructures. Although the interferometric method is widely used for ground deformation investigations, using displacement data from satellite observation in structural monitoring is less investigated. The joint use of multi-frequency satellite radar data provided by the European Space Agency Copernicus project and Italian Space Agency will be explored. The paper introduces the workflow implemented for processing satellite radar data from the X-band COSMO-SkyMed constellation by the Italian Space Agency over the municipality of Modena (Italy). An open-source workflow based on Multi-Temporal Interferometric technique and Persistent Scatterers Interferometry is adopted, enabling the detection of displacements of stable targets and the generation of corresponding time series. Radar data products, derived from the processing of both COSMO-SkyMed and Sentinel-1 data, are analyzed in a Geographic Information System alongside the available geospatial dataset of infrastructures. This approach enables the extraction of displacement components related to the ground and infrastructures. The method’s potential for characterizing infrastructures behaviour is assessed through the analysis of selected case studies. The results aim to establish the foundations for a method capable of assessing infrastructure safety.

Assessing landslide susceptibility and dynamics at cultural heritage sites by integrating machine learning techniques and persistent scatterer interferometry - José Eduardo Bonini; Carlotta Parenti; Francesca Grassi; Francesco Mancini; Bianca Carvalho Vieira; Mauro Soldati (Geomorphology, 2025)

Greenhouse gas Emissions Deployment (GED): A novel Lean method for mitigating greenhouse gas emissions in industrial environment - Marcello Braglia; Francesco Di Paco; Roberto Gabbrielli; Carlo Grassi; Leonardo Marrazzini (Sustainable Production and Consumption, 2024)

Wandering outside of the S tyx: Surface activity of an iconic subterranean vertebrate, the olm ( Proteus anguinus ) - Raoul Manenti; Matteo Riccardo Di Nicola; Veronica Zampieri; Giorgio Grassi; Thomas Creanza; Edgardo Mauri; Gentile Francesco Ficetola; Benedetta Barzaghi (Ecology, 2024)

Effect of chest physiotherapy on cystic fibrosis sputum nanostructure: an experimental and theoretical approach - Michela Abrami; Massimo Maschio; Massimo Conese; Marco Confalonieri; Francesco Salton; Fabio Gerin; Barbara Dapas; Rossella Farra; Alessandra Adrover; Gesmi Milcovich; Claudia Fornasier; Alice Biasin; et al. (Drug Delivery and Translational Research, 2022)
Cystic fibrosis (CF) is a disease characterized by the production of viscous mucoid secretions in multiple organs, particularly the airways. The pathological increase of proteins, mucin and biological polymers determines their arrangement into a three-dimensional polymeric network, affecting the whole mucus and impairing the muco-ciliary clearance which promotes inflammation and bacterial infection. Thus, to improve the efficacy of the drugs usually applied in CF therapy (e.g., mucolytics, anti-inflammatory and antibiotics), an in-depth understanding of the mucus nanostructure is of utmost importance. Drug diffusivity inside a gel-like system depends on the ratio between the diffusing drug molecule radius and the mesh size of the network. Based on our previous findings, we propose the combined use of rheology and low field NMR to study the mesh size distribution of the sputum from CF patients. Specifically, we herein explore the effects of chest physiotherapy on CF sputum characteristic as evaluated by rheology, low field NMR and the drug penetration through the mucus via mathematical simulation. These data show that chest physiotherapy has beneficial effects on patients, as it favourably modifies sputum and enhances drug penetration through the respiratory mucus. Graphical abstract

3D subsoil reconstruction of a mud volcano in central Sicily by means of geophysical surveys - Sabrina Grassi; Giorgio De Guidi; Graziano Patti; Fabio Brighenti; Francesco Carnemolla; Sebastiano Imposa (Acta Geophysica, 2022)
The upwelling of fluids, subject to overpressure, along with discontinuities in the subsoil, causes the formation of geological structures known as mud volcanoes. These structures, very widespread in the world and in some cases located near inhabited centers, can represent a considerable risk factor for the population, as they can give rise to paroxysmal eruptions, even very violent. The assessment of the characteristics and structure of the subsoil of the areas affected by this phenomenon can prove to be a useful tool for risk mitigation. Non-invasive geophysical surveys were carried out in the area of the active cone of the Santa Barbara mud volcano in order to obtain a 3D characterization of the subsoil. Through the processing and integration of data derived from active and passive seismic surveys was obtained, a 3D model showing the seismostratigraphic subsoil structure. The electrical resistivity tomography surveys provided results comparable to those obtained from seismic surveys and supplied information on the perimetral areas of the mud volcano. The information obtained is useful to study the boundary conditions that influence short-scale activity. Furthermore, this study seeks to evaluate the possibility of using the proposed methodological approach for monitoring the variations that occur over time in the areas affected by mud volcanoes phenomenon.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The art gallery maze: a novel tool to assess human navigational abilities - Hamed Taheri Gorji; Michela Leocadi; Francesco Grassi; Gaspare Galati (Cognitive Processing, 2021)

The impact of interventions in the global land and agri‐food sectors on Nature’s Contributions to People and the UN Sustainable Development Goals - Pamela McElwee; Katherine Calvin; Donovan Campbell; Francesco Cherubini; Giacomo Grassi; Vladimir Korotkov; Anh Le Hoang; Shuaib Lwasa; Johnson Nkem; Ephraim Nkonya; Nobuko Saigusa; Jean‐Francois Soussana; et al. (Global Change Biology, 2020)
Interlocked challenges of climate change, biodiversity loss, and land degradation require transformative interventions in the land management and food production sectors to reduce carbon emissions, strengthen adaptive capacity, and increase food security. However, deciding which interventions to pursue and understanding their relative co‐benefits with and trade‐offs against different social and environmental goals have been difficult without comparisons across a range of possible actions. This study examined 40 different options, implemented through land management, value chains, or risk management, for their relative impacts across 18 Nature's Contributions to People (NCPs) and the 17 Sustainable Development Goals (SDGs). We find that a relatively small number of interventions show positive synergies with both SDGs and NCPs with no significant adverse trade‐offs; these include improved cropland management, improved grazing land management, improved livestock management, agroforestry, integrated water management, increased soil organic carbon content, reduced soil erosion, salinization, and compaction, fire management, reduced landslides and hazards, reduced pollution, reduced post‐harvest losses, improved energy use in food systems, and disaster risk management. Several interventions show potentially significant negative impacts on both SDGs and NCPs; these include bioenergy and bioenergy with carbon capture and storage, afforestation, and some risk sharing measures, like commercial crop insurance. Our results demonstrate that a better understanding of co‐benefits and trade‐offs of different policy approaches can help decision‐makers choose the more effective, or at the very minimum, more benign interventions for implementation.

Which practices co‐deliver food security, climate change mitigation and adaptation, and combat land degradation and desertification? - Pete Smith; Katherine Calvin; Johnson Nkem; Donovan Campbell; Francesco Cherubini; Giacomo Grassi; Vladimir Korotkov; Anh Le Hoang; Shuaib Lwasa; Pamela McElwee; Ephraim Nkonya; Nobuko Saigusa; et al. (Global Change Biology, 2020)
There is a clear need for transformative change in the land management and food production sectors to address the global land challenges of climate change mitigation, climate change adaptation, combatting land degradation and desertification, and delivering food security (referred to hereafter as “land challenges”). We assess the potential for 40 practices to address these land challenges and find that: Nine options deliver medium to large benefits for all four land challenges. A further two options have no global estimates for adaptation, but have medium to large benefits for all other land challenges. Five options have large mitigation potential (>3 Gt CO 2 eq/year) without adverse impacts on the other land challenges. Five options have moderate mitigation potential, with no adverse impacts on the other land challenges. Sixteen practices have large adaptation potential (>25 million people benefit), without adverse side effects on other land challenges. Most practices can be applied without competing for available land. However, seven options could result in competition for land. A large number of practices do not require dedicated land, including several land management options, all value chain options, and all risk management options. Four options could greatly increase competition for land if applied at a large scale, though the impact is scale and context specific, highlighting the need for safeguards to ensure that expansion of land for mitigation does not impact natural systems and food security. A number of practices, such as increased food productivity, dietary change and reduced food loss and waste, can reduce demand for land conversion, thereby potentially freeing‐up land and creating opportunities for enhanced implementation of other practices, making them important components of portfolios of practices to address the combined land challenges.

Environmental quality and hygienic safety of the Alimini Lakes (Puglia, Italy): 20 years of monitoring (1995–2014) - Antonella De Donno; Francesco Bagordo; Francesca Serio; Tiziana Grassi; Gabriele Devoti; Marcello Guido (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Using the DPSIR framework to identify factors influencing the quality of groundwater in Grecìa Salentina (Puglia, Italy) - Francesco Bagordo; Danilo Migoni; Tiziana Grassi; Francesca Serio; Adele Idolo; Marcello Guido; Nicola Zaccarelli; Francesco Paolo Fanizzi; Antonella De Donno (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Efficient synthesis of highly substituted tetrahydroindazolone derivatives - Angela Scala; Anna Piperno; Francesco Risitano; Santa Cirmi; Michele Navarra; Giovanni Grassi (Molecular Diversity, 2015)

Rotavirus Occurrence in Shellfish with Low Levels of E. coli - Francesco Bagordo; Tiziana Grassi; Adele Idolo; Francesca Serio; Giovanni Gabutti; Antonella De Donno (Food and Environmental Virology, 2013)

Aldol-type compounds from water-soluble indole-3,4-diones: synthesis, kinetics, and antiviral properties - Angela Scala; Massimiliano Cordaro; Antonino Mazzaglia; Francesco Risitano; Assunta Venuti; Maria Teresa Sciortino; Giovanni Grassi (Molecular Diversity, 2013)

Detection of Viruses in Coastal Seawater Using Mytilus Galloprovincialis as an Accumulation Matrix - Antonella De Donno; Tiziana Grassi; Francesco Bagordo; Adele Idolo; Francesca Serio; Giovanni Gabutti (Food and Environmental Virology, 2012)

Diastereoselective multicomponent synthesis and anti-HSV-1 evaluation of dihydrofuran-fused derivatives - Angela Scala; Massimiliano Cordaro; Francesco Risitano; Ivana Colao; Assunta Venuti; Maria Teresa Sciortino; Patrizia Primerano; Giovanni Grassi (Molecular Diversity, 2012)

Rotavirus detection in environmental water samples by tangential flow ultrafiltration and RT-nested PCR - Tiziana Grassi; Francesco Bagordo; Adele Idolo; Federica Lugoli; Giovanni Gabutti; Antonella De Donno (Environmental Monitoring and Assessment, 2010)

Contribution of diffusional and non-diffusional limitations to midday depression of photosynthesis in Arbutus unedo L. - Giacomo Grassi; Francesco Ripullone; Marco Borghetti; Sabrina Raddi; Federico Magnani (Trees, 2009)

Inhibitory effects of fenofibrate on apoptosis and cell proliferation in human endothelial cells in high glucose - Michela Zanetti; Alessia Stocca; Barbara Dapas; Rossella Farra; Laura Uxa; Alessandra Bosutti; Rocco Barazzoni; Fleur Bossi; Carlo Giansante; Francesco Tedesco; Luigi Cattin; Gianfranco Guarnieri; et al. (Journal of Molecular Medicine, 2008)

The death receptor DR5 is involved in TRAIL-mediated human osteoclast apoptosis - Silvia Colucci; Giacomina Brunetti; Francesco Paolo Cantatore; Angela Oranger; Giorgio Mori; Paolo Pignataro; Roberto Tamma; Felice Roberto Grassi; Alberta Zallone; Maria Grano (Apoptosis, 2007)

Human osteoclasts express different CXC chemokines depending on cell culture substrate: molecular and immunocytochemical evidence of high levels of CXCL10 and CXCL12 - Francesco Grassi; Anna Piacentini; Sandra Cristino; Stefania Toneguzzi; Carola Cavallo; Andrea Facchini; Gina Lisignoli (Histochemistry and Cell Biology, 2003)

IL1-? and TNF-? induce changes in the nuclear polyphosphoinositide signalling system in osteoblasts similar to that occurring in patients with rheumatoid arthritis: an immunochemical and immunocytochemical study - Nicoletta Zini; Gina Lisignoli; Liliana Solimando; Alberto Bavelloni; Francesco Grassi; Lia Guidotti; Carmela Trimarchi; Andrea Facchini; Nadir Mario Maraldi (Histochemistry and Cell Biology, 2003)

Age-associated changes in functional response to CXCR3 and CXCR5 chemokine receptors in human osteoblasts - Gina Lisignoli; Anna Piacentini; Stefania Toneguzzi; Francesco Grassi; Matilde Tschon; Sandra Cristino; Andrea Facchini; Erminia Mariani (Biogerontology, 2003)